On-site weld quality assessment and qualification for stainless steels tanks - Guilherme, Luis Henrique; Fugivara, Cecilio Sadao; Benedetti, Assis Vicente (Eclética Química, 2022)
Stainless steel tanks are frequently degraded by localized corrosion in bioprocess industries. A case study of 2101 duplex stainless steel tank allowed to apply a portable electrochemical microcell system (PassivityScan) for on-site weld inspection and corrosion monitoring from the manufacturing until 12 months of operation. During the tank manufacturing, the double loop electrochemical potentiokinetic reactivation technique was applied to measure the sensitization degree on the welded regions. The manufactured tank was submitted to the passivation treatment to improve the passivation properties and corrosion resistance. On-site cyclic polarization tests were performed and confirmed the increase of passivation level of treated surface. The passivation level was measured again after 12 months of operation and detected a lower passivation level compared to the initial passivated surface, indicating that the passivation treatment lost its effect after that period. Therefore, an acceptance criterion to passivation level was empirically determined. PassivityScan is an advanced device to qualify the welds and the passivated surfaces, and useful for corrosion monitoring and the reliability maintenance.